Chronic diseases among university students: prevalence, patterns and impact on health-related quality of life - Gazibara, Tatjana; Pekmezović, Tatjana; Popović, Aleksandra; Paunić, Mila; Kisić Tepavčević, Darija (Vojnosanitetski pregled, 2021)
Background/Aim. Around 30% of university students have chronic diseases and/or special care needs. As future taskforce in various job sectors will be drawn from current university student population, it is essential that their health-related problems are recognized and properly managed. The aims of this study were to estimate the prevalence and patterns of chronic diseases in the university student population and to assess their health-related quality of life (HRQoL). Methods. A total of 1,624 Belgrade University students were recruited from April to June 2009 at the Student Public Health Center. The students filled in sociodemographic and behavioral questionnaire, the Beck Depression Inventory (BDI) and the SF-36 questionnaire. Data on chronic diseases were self-reported and thereafter validated in medical records. The impact of chronic diseases on HRQoL was evaluated through series of linear regression models. Results. The prevalence of chronic diseases was 16.5%. The most common chronic diseases were asthma and chronic bronchitis (4.2% and 3.1%, respectively). All SF-36 domains, both composite and total scores were lower compared to healthy students (p
Keywords: chronic disease; prevalence; students; quality of life; surveys and questionnaires.